Sosialisasi Manajemen Budidaya Sapi Indukan pada Kelompok Tani Harapan Sejahtera - Riesi Sriagtula; Yetmaneli; Ida Indrayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Community service activities were designed to enhance the productivity of breeding cattle through the socialization of breeding cattle cultivation management at the Harapan Sejahtera Farmers Group in Padang City. The methods used included surveys, counseling, discussions, and assistance applying breeding cattle cultivation management. However, the key to enhancing the insight and skills of farmers in implementing cattle breeding management, such as pens and feeding, was the comparative study and a short internship for two days at CV. Andalas Farm, a beef cattle farming business. This practical learning approach provided farmers with firsthand experience and insight into modern maintenance techniques, including pen management and feeding. Innovation at CV. Andalas Farm, which processes sweet corn harvesting waste into silage as a source of green fodder to replace grass, has increased the skills of farmers. The activities increased farmers' knowledge and skills about cattle farming management, especially pen and feed management.